Surface Environmental Evolution Monitoring in Coal Mining Subsidence Area Based on Multi-Source Remote Sensing Data - Shang, Hui; Zhan, Hui-Zhu; Ni, Wan-Kui; Liu, Yang; Gan, Zhi-Hui; Liu, Si-Hang (Frontiers in Earth Science, 2022)
The exploitation of mineral resources is crucial for cost-effective construction but has also led to severe damage to the ecological environment in mining areas. Therefore, it is particularly important to effectively monitor surface environmental problems in the mining subsidence area caused by the exploitation of mineral resources. Herein, the Huinong coal mining subsidence area, Shizuishan city, Ningxia, China, was taken as the study area. The remote sensing image features of various environmental elements were investigated through field investigations, the measured spectra, and image spectrum contrast analysis. On this basis, an object-oriented random forest classification method was used to classify images from different time phases and sources in coal mining subsidence areas. Next, the man–machine interactive interpretation was confirmed by referring to the pre-classification results. By overlaying the interpretation result map and analyzing the land-use class changes, the spatial–temporal evolution monitoring of the surface environment in the coal mining subsidence area from 1979 to 2018 was carried out. The results show that the surface environment in the coal mining subsidence area has undergone significant changes over the past 40 years, among which—from 1979 to 2003—the environment of the coal mining area was severely damaged by the intensive mining activities. The area of cultivated land and vegetation coverage decreased sharply, while the area of other land-use classes, such as coal heaps, water bodies, and coal gangue, exhibited a trend of rapid growth. From 2003 to 2018, after more than 10 years of mine geological environment renovation and management, the surface environment of the coal mining subsidence area greatly improved, among which the vegetation coverage has shown the fastest growth rate, while the area of coal gangue, badlands, and other land-use classes have significantly reduced. The hidden dangers of geological disasters have been drastically mitigated. In addition, the residential area continued to decrease in the early stages and then rebounded to a certain extent, indicating that urbanization was carried out at the same time as the ecological environment began to improve. The surface environment before and after the renovation is consistent with the results from remote sensing monitoring.